Inclusive engineering classroom learning communities: reflections and lessons learned from three partner institutions - Vaden, Jessica M.; Brooks, Amy L.; Dukes, April A.; Parrish, Kristen; Hermundstad Nave, Amy; Landis, Amy; Bilec, Melissa M. (Frontiers in Education, 2025)
IntroductionTeaching and learning are not often highlighted in research-intensive science,technology, engineering, and mathematics (STEM) graduate training. Thus, many faculty in STEM fields are unfamiliar with the ways educational theories can inform how to transform their teaching to reflect the contextual awareness and critical sensibilities needed to lead diverse groups of students. Professional development has traditionally served as the “on-the-job training” for faculty and instructors to improve their teaching skills, and communities of practice, such as faculty learning communities (FLCs), have emerged as a promising training outlet, including for inclusive teaching practices.MethodsTo explore faculty’s implementation of inclusive practices, we convened inclusivity-focused FLCs at three partner institutions across different institutional levels (i.e., department-, school-, and institution-wide). To this end, we conducted surveys and experiential interviews with faculty participants, including those who also served as FLC facilitators, from each institution.ResultsThe faculty participants reported positively on their experiences within their FLCs, and they provided feedback that resulted in three key findings: (1) institutional context must be considered when developing and planning FLCs, (2) catalyzing trust and vulnerability are required for inclusivity-focused FLCs, and (3) sustaining active engagement from FLC members can be difficult given institutional opportunities and faculty demands.DiscussionThese findings can help inform improvements to FLC implementation and support faculty in adopting inclusive strategies in their classrooms, ultimately creating better learning environments for students. This study’s findings, discussion, and conclusions are likely to be interesting to engineering and STEM faculty, faculty developers, and university leadership seeking to weave inclusivity into their classroom culture.